Australian compilation of seismic-derived bathymetry - Ulysse Lebrec; Victorien Paumard; Juliette Denudt; Catherine Du Réau; Simon C. Lang; Julien Bailleul (Scientific Data)
Abstract This article presents a national seismic-derived bathymetric compilation based on the integration of 253 3D seismic surveys. Individual surveys were combined to produce four regional compilations covering an area of 267,000 km2, with a spatial resolution of 30 × 30 m and a vertical accuracy of 5 m + 5%d. The production of the dataset is based on the integration of seismic survey first returns with seismic vessel echosounder measurements. Following the extraction of the depth soundings, all data points were converted from time to depth using synthetic velocity profiles and filtered to remove erroneous records. The seismic survey’s first returns were corrected using navigation depth soundings to account for geometric distortions. All depth values were reduced to WGS84 and EGM2008 datum. A comparison of the seismic-derived bathymetry with multibeam echosounder surveys suggests that where a thin layer of loose sediments overlies a lithified substratum, the seismic first return captures the top of the substratum.